Inter-cultural and cross-cultural communication through physicians’ lens: perceptions and experiences - Shirazi, Mandana (Int J Med Educ, 2020)
OBJECTIVES: This study aimed to explore Swedish physicians’ perceptions regarding physician-patient communication in an Iranian context and to obtain a deeper understanding of their lived experience when encountering Middle Eastern and Swedish patients in their daily work. METHODS: This is a multi-method study, including conventional content analysis in combination with phenomenological methodology. A triangulation approach to data collection and analysis was used. Serving the purpose of the study, twelve Swedish physicians with previous experience of Middle Eastern patients were purposely selected to participate in the study. They watched a video showing simulated patient encounter in an Iranian context. The video served as a trigger. Semi-structured interviews were conducted focusing on the participants’ perceptions of the video and their lived experiences. Constant comparative analysis was used for a deep understanding of the data. RESULTS: The core themes were cultural diversity, doctor-centeredness, and patient-centeredness. Cultural diversity was a convergent theme and included trust, interpersonal interaction, context, and doctor dominancy. Patient-centeredness and doctor-centeredness were divergent themes and included doctors’ authority, equity, the experience of illness, and accountability. CONCLUSIONS: The participants confirmed large cultural differences in doctor-patient communication when encountering Iranian and Swedish patients. Inter-cultural and cross-cultural competencies were made visible. To be able to appreciate other cultures’ health values, beliefs, and behaviors, increased cultural competence in health care is of importance.